The Factors which Affect the Nursing Students’ Eating Attitude - Kim, Hee-Jeong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study attempted to identify the stress, depression, self- control and eating attitude of nursing college students and to provide basic data for healthy eating behavior program of nursing college students. Methods/Statistical analysis: The subjects of this study were 187 nursing college students were investigated. Data collection period was collected from March 1, 2019 to July 30, 2019. Statistical methods used were frequency, mean, standard deviation, t-test and ANOVA. Also Pearson’s correlation analysis and regression analysis were used. Findings: According to the study, there was a statistically significant positive correlation (r= .668, p<.01) between stress and with eating attitude and statistically significant positive correlation (r = .342, p<.001) between depression and eating attitude. Additionally there was statistically significant negative correlation (r=–.412, p<.001) between self-control and eating attitude. Also independent variables that have a significant effect on eating attitude were stress (β =. 46, p <.001), depression (β =- .25, p = .002), and self-control (β =- -.28, p = .003). Improvements/Applications: Based on these results, customized education by grade needs to be implemented to develop healthy eating attitudes, and programs should be planned to improve self-control and reduce stress and depression to manage the correct eating attitude.